2022
DOI: 10.1186/s12871-022-01779-2
|View full text |Cite
|
Sign up to set email alerts
|

Total intravenous anesthesia induced and maintained by a combination of remimazolam and remifentanil without a neuromuscular blocking agent: a prospective, observational pilot study

Abstract: Background A novel short-acting benzodiazepine, Remimazolam, has recently been approved for general anesthesia and sedation. Hence, we investigated the feasibility and safety of remimazolam during the induction and maintenance of general anesthesia without using a neuromuscular blocking agent (NMBA) in patients undergoing hysteroscopic surgery. Methods This prospective observational study included 38 patients undergoing hysteroscopic surgery. Remim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…28 In addition, intra-operative BIS values were reported to increase to more than 60 even when patients were confirmed to reach sufficient hypnotic levels for general anaesthesia based on other hypnotic depth indicators, such as spectral edge frequency and pupil diameter. 7 Moreover, BIS value took approximately twice as long (135 s) to fall to less than 60 as the time taken to achieve an MOAA/S score of 1 or less (63 s), 8 and it did not correlate well with loss of consciousness in remimazolam anaesthesia. 2,8,29 Notably, in our study, BIS values during word presentation for 15 min were maintained at more than 60 (60 to 80) for more than 13.5 min despite a MOAA/S score of 2 or less.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…28 In addition, intra-operative BIS values were reported to increase to more than 60 even when patients were confirmed to reach sufficient hypnotic levels for general anaesthesia based on other hypnotic depth indicators, such as spectral edge frequency and pupil diameter. 7 Moreover, BIS value took approximately twice as long (135 s) to fall to less than 60 as the time taken to achieve an MOAA/S score of 1 or less (63 s), 8 and it did not correlate well with loss of consciousness in remimazolam anaesthesia. 2,8,29 Notably, in our study, BIS values during word presentation for 15 min were maintained at more than 60 (60 to 80) for more than 13.5 min despite a MOAA/S score of 2 or less.…”
Section: Discussionmentioning
confidence: 97%
“…4,5 However, the bispectral index (BIS TM , Medtronic, Dublin, Ireland) of some patients administered remimazolam for general anaesthesia cannot be maintained at less than 60, typically recommended for general anaesthesia, even if they have been given the maximum dose, 12 mg kg À1 h À1 for induction and 2 mg kg À1 h À1 for maintenance. [6][7][8] Postoperative interviews suggested that most patients had no memory formation during remimazolam anaesthesia at the level associated with a BIS of more than 60. 7,8 Nevertheless, we cannot be certain that memory formation did not occur solely based on the current evidence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remimazolam is a novel, ultra-short acting benzodiazepine, combining the pharmacodynamic profile of midazolam with a speed of onset and breakdown similar to remifentanil. Its use has been described for both procedural sedation and as part of a TIVA regimen along with an opioid [23]. Anaesthetic drugs and benzodiazepines bind to the gamma-aminobutyric acid A receptor at both distinct and overlapping sites.…”
Section: Regional Anaesthesia and Adjunctsmentioning
confidence: 99%